Evaluation of the biocontrol potential of Aspergillus welwitschiae against the root-knot nematode Meloidogyne graminicola in rice (Oryza sativa L.) - Ying LIU; Zhong DING; De-liang PENG; Shi-ming LIU; Ling-an KONG; Huan PENG; Chao XIANG; Zhong-cai LI; Wen-kun HUANG (Journal of Integrative Agriculture, 2019)
The root-knot nematode Meloidogyne graminicola is considered one of the most devastating pests in rice-producing areas, and nematicides are neither ecofriendly nor cost effective. More acceptable biological agents are required for controlling this destructive pathogen. In this study, the biocontrol potential of Aspergillus welwitschiae AW2017 was investigated in laboratory and greenhouse experiments. The in vitro ovicidal and larvicidal activities of A. welwitschiae metabolites were tested on M. graminicola in laboratory experiments. The effect of A. welwitschiae on the attraction of M. graminicola to rice and the infection of rice by M. graminicola was evaluated in a greenhouse. The bioagent AW2017 displayed good nematicidal potential via its ovicidal and larvicidal action. The best larvicidal activity was observed at a concentration of 5×AW2017, which caused an 86.2% mortality rate at 48 h post inoculation. The highest ovicidal activity was recorded at a concentration of 5×AW2017, which resulted in an approximately 47.3% reduction in egg hatching after 8 d compared to the control. Under greenhouse conditions, the application of A. welwitschiae significantly reduced the root galls and nematodes in rice roots compared to the control. At a concentration of 5×AW2017, juveniles and root galls in rice roots at 14 d post inoculation (dpi) were reduced by 24.5 and 40.5%, respectively. In addition, the attraction of M. graminicola to rice roots was significantly decreased in the AW2017 treatment, and the development of nematodes in the AW2017-treated plants was slightly delayed compared with that in the PDB-treated control plants. The results indicate that A. welwitschiae is a potential biological control agent against M. graminicola in rice.